Postoperative complications of minimally invasive esophagectomy for esophageal cancer. Issue 2 (12th February 2020) - Ozawa, Soji; Koyanagi, Kazuo; Ninomiya, Yamato; Yatabe, Kentaro; Higuchi, Tadashi
Abstract: Minimally invasive esophagectomy (MIE) has been performed increasingly more frequently for the treatment of esophageal cancer, ever since it was first described in 1992. However, the incidence of postoperative complications of MIE has not yet been well‐characterized, because (a) there are few reports of studies with a sufficient sample size, (b) a variety of minimally invasive surgical techniques are used, and (c) there are few reports in which an established system for classifying the severity of complications is examined. According to an analysis performed by the Esophageal Complications Consensus Group, the most common complications of MIE are pneumonia, arrhythmia, anastomotic leakage, conduit necrosis, chylothorax, and recurrent laryngeal nerve palsy. Therefore, we decided to focus on these complications. We selected 48 out of 1245 reports of studies (a) that included more than 50 patients each, (b) in which the esophagectomy technique used was clearly described, and (c) in which the complications were adequately described. The overall incidences of the postoperative complications of MIE for esophageal cancer were analyzed according to the MIE technique adopted, that is, McKeown MIE, Ivor Lewis MIE, robotic‐assisted McKeown MIE, robotic‐assisted Ivor Lewis MIE, or mediastinoscopic transmediastinal esophagectomy. Pneumonia, arrhythmia, anastomotic leakage, and recurrent laryngeal nerve palsy occurred at an incidence rate of about 10% each; Ivor Lewis MIE was associated with a relatively low incidence of recurrent laryngeal nerve palsy. It is important to recognize that the incidences of complications of MIE are influenced by the MIE technique adopted and the extent of lymph node dissection. Abstract : The overall incidences of the postoperative complications of MIE for esophageal cancer were analyzed according to the MIE technique adopted, that is, McKeown MIE, Ivor Lewis MIE, robotic‐assisted McKeown MIE, robotic‐assisted Ivor Lewis MIE, or mediastinoscopic transmediastinal esophagectomy. Pneumonia, arrhythmia, anastomotic leakage, and recurrent laryngeal nerve palsy occurred at an incidence rate of about 10% each; Ivor Lewis MIE was associated with a relatively low incidence of recurrent laryngeal nerve palsy. It is important to recognize that the incidences of complications of MIE are influenced by the MIE technique adopted and the extent of lymph node dissection.